2013
DOI: 10.1016/j.urology.2012.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Rho-kinase Inhibitor Azaindole-1 Has Long-lasting Erectile Activity in the Rat

Abstract: Objectives To investigate the effects of the selective Rho-kinase (ROCK) inhibitor azaindole-1 on erectile function under physiologic and pathophysiologic conditions in the rat. Methods The effect of intracavernosal (i.c.) injections of azaindole-1 on change in ICP, ICP/MAP, AUC, and response duration were investigated in the anesthetized rat under control conditions and when NANC neurotransmission and cholinergic function or sGC were inhibited or after cavernosal nerve crush injury. Results The i.c. injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…ODQ (Cayman) was also dissolved in the Transcutol-Cremophor vehicle. The dose of ODQ used in these experiments was determined from pilot experiments and reports in the literature (17). No financial support was provided by Bayer.…”
Section: Methodsmentioning
confidence: 99%
“…ODQ (Cayman) was also dissolved in the Transcutol-Cremophor vehicle. The dose of ODQ used in these experiments was determined from pilot experiments and reports in the literature (17). No financial support was provided by Bayer.…”
Section: Methodsmentioning
confidence: 99%
“…More recently developed ROCK inhibitors, including azaindole-1 and SAR407899, have shown promise in recovering erections in preclinical rat studies. 4547 Azaindole-1, a more selective ROCK inhibitor with less secondary kinase inhibition than Y-27632 and fasudil, demonstrated both antihypertensive and proerectile effects. 45,46 …”
Section: No and Rhoa–rock In Ed Pathologymentioning
confidence: 99%
“…Azaindole-1, a newer, selective ROCK inhibitor, improves ED in rats after nerve-crush injury and has antihypertensive effects when given systemically, but it is not currently being evaluated for ED in a clinical trial. 45,46 …”
Section: Current Clinical Use Of Rock Inhibitorsmentioning
confidence: 99%
“…The isolated enzyme studies of Zhao and Marletta showed that ODQ had no effect on basal activity of sGC but blocked the activation of sGC by NO (89). Treatment with ODQ will inhibit the erectile response to NO donors, to cavernosal nerve stimulation, and to sGC stimulators like BAY 41-8543 (50,51). However, when sGC is inactivated by ODQ, the effect of the sGC activator BAY 60-2770, which has potent erectile activity, will be increased (51a).…”
Section: Sgc Stimulators and Activatorsmentioning
confidence: 99%
“…These studies demonstrated that the heme-free enzyme could be activated to increase the formation of cGMP from GTP and led to the concept that new classes of agents could be effective in targeting an oxidized or heme-free enzyme (33,44,72,79,80). In experimental animals, sGC can be inhibited and made insensitive to NO by treatment with 1H [1,2,4]oxadiazolo-[4,3-a]quinoxalin-1-one (ODQ), an agent that has been shown to oxidize the heme iron on the enzyme in many isolated tissue studies and in a few in vivo studies (18,23,51,56,57,65,89). The isolated enzyme studies of Zhao and Marletta showed that ODQ had no effect on basal activity of sGC but blocked the activation of sGC by NO (89).…”
Section: Sgc Stimulators and Activatorsmentioning
confidence: 99%